Running Away from Authority to Gain Recognition (The Case of Indonesian Interfaith Marriage Overseas) - Sri Wahyuni (AIUA Journal of Islamic Education, 2019)
This article discusses about the regulation of state authorities for the interfaith marriage in Indonesia; the recognition of state authorities for the interfaith marriages are carried out by citizen abroad; and what is the meaning of state recognition for them. This is a law research that takes an anthropological pattern. Indonesia as a modern nation state has authority to regulate the marriage of citizen. The state also gives authority to the religion for the recognition of the validity of marriage, as Section 2 (1) of Act No. 1 of 1974 on the marriage Marriage. Relating to interfaith marriage is also based on that article, so that the religious authorities determine its validity. It’s difficult to be conducted in Indonesia.Regulation of Indonesian State authority for citizen marriage overseas is in Article 56 (1) and (2). According to the article, the state of Indonesia also has authority over the marriage of its citizens abroad, both in the implementation of the marriage (that must follow the local law and Indonesian law) and authority to record after the citizens returned to Indonesia. In the practice, State authorities in the marriage registration is only administratively population recording, without regarding the validity of the marriage. This registration is also for the interfaith marriage abroad. Therefore, the State authorities can also recognize interfaith marriages of Indonesian citizens abroad upon arrival in Indonesia, while it’s difficult to be implemented in Indonesia.They also get a marriage certificate for their marriage abroad as a symbol of recognition from an authority. With the certificate, they fully get their rights as well as the marriages performed in Indonesia which are recognized by the authority of the Indonesian State. Among those rights are the rights to survival and the consequences of legal marriage and the right to offspring.